The determining role of magnetic field in iron and alloy carbide precipitation behaviors under the external field. (15th July 2016) - Hou, T.P.; Peet, M.J.; Hulme-Smith, C.N.; Wu, K.M.; Li, Y.; Guo, L.
Abstract: A combined approach to calculate the thermodynamic properties of iron and alloy carbides including the thermal and magnetic contribution is derived. Special emphasis is placed on the role of Fe and Mo to the Gibbs free energy. Lower Mo concentration in the carbides corresponds to a higher thermal Gibbs free energy change. The higher Fe content and external magnetic field greatly increase the induced magnetization, reducing the magnetic Gibbs free energy substantially and therefore increase the formation temperature. The stability of M2 C and M3 C are mainly determined by the thermal factors, whereas magnetic field has a predominant contribution for M6 C. Graphical abstract: